SHARIAH COMPLIANCE ON RETAKAFUL IN MALAYSIA - Nurwajihah Ajlaa Ali; Ruzian Markom (Fakultas Hukum, Universitas Diponegoro, 2021)
Retakaful is an Islamic alternative to the reinsurance industry in ensuring the stability of takaful companies. In Malaysia, the takaful operators need to depend on retakaful operators to ensure the takaful industry's long-term continuity by sharing the risk with the retakaful operators due to the small numbers of takaful operators. As a result, they reinsure their Takaful with the conventional reinsurance companies to meet the market demand. This practice continues to be acceptable based on an argument of unavoidable circumstances such as a necessity (darurah) and a dire need (hajah) due to insufficient retakaful companies. The Shari'ah issues arose on the needs for retakaful operators with conventional reinsurers or operators. Therefore, the paper aims to analyze the role of retakaful and its potential within the industry by identifying. Then it explores the Shari'ah principle and the arguments, existing rules, and regulations on the said issues. This study utilized the doctrinal research method with the content analysis. The data is collected from the library consisting of primary and secondary sources. The study's findings revealed that the Shariah scholars resolution plays essential roles in enhancing the roles of the retakaful industry based on darurah and hajah.